1993
DOI: 10.1007/bf01969922
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the renal injury caused by liver ischemia-reperfusion in rats

Abstract: To explain the mechanism of renal injury caused by liver ischemia-reperfusion, we investigated biochemical and morphological changes in the liver and kidney in rats. After reperfusion following 60 min of liver ischemia, numerous changes were found. The level of serum transaminases and lipid peroxide formation in the liver tissue increased significantly. Electron microscopic studies revealed that most of the hepatocytes had swollen mitochondria and clumping of the nuclear chromatin. The sinusoidal endothelium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
2
2
0
2
Order By: Relevance
“…Correspondingly, the kidneys from rats subjected to liver IR showed little morphological damage and they failed to see increases in apoptosis (caspase-3) and neutrophil infiltration (myeloperoxidase activity). Their study confirms previous observations in rats that renal dysfunction was mild with little or no histological changes after liver IR (9,41). Polat et al .…”
Section: Discussionsupporting
confidence: 91%
“…Correspondingly, the kidneys from rats subjected to liver IR showed little morphological damage and they failed to see increases in apoptosis (caspase-3) and neutrophil infiltration (myeloperoxidase activity). Their study confirms previous observations in rats that renal dysfunction was mild with little or no histological changes after liver IR (9,41). Polat et al .…”
Section: Discussionsupporting
confidence: 91%
“…Morphological alterations in the liver and kidneys following liver I/R injury were also reported including degeneration in hepatocytes, congestion, and necrosis in the liver and degeneration in the renal tubular epithelium, tubular dilatation with loss of brush border, congestion, leukocyte infiltration, hyaline cast in the kidney. Similar findings were observed in previous studies [5,11,[14][15][16][17] suggesting that hepatic I/R injury damages both the morphology and the function of the kidney [16,18,19]. Moreover, several studies reported pathological alterations in kidneys according to the period of reperfusion ranging from 1 to 24 h. After 1-h kidney showed moderate hemorrhage and congestion [20], eosinophilic appearance and perinuclear vacuolic formation in tubular cells [17] after 8 h showing loss of brush border and tubular epithelium with hyaline casts and congestion [21], while other researches showed tubular dilatation and necrosis, cellular swelling, and granular casts after 24-h reperfusion [5,14,22].…”
Section: Discussionsupporting
confidence: 90%
“…A B C of Polat et al (2006) on rats showed no or little morphological damage of the kidney subjected to 45 min total hepatic ischemia followed by 1 hour of reperfusion. On the other hand, Lee et al (2009) showed that mice subjected to 60 min partial liver ischemia develop severe AKI in less than 24 h. During reperfusion following 60 min of liver ischemia, numerous changes were found including biochemical and renal morphological injury as well as increase in endotoxin, lipid peroxide, and lysosomal enzymes in the blood (Kudo et al 1993). Remote organ injuries are largely consequences of the endogenously produced mediators rather than the exogenous factors and toxins (Weinbroum et al 1999).…”
Section: Discussionmentioning
confidence: 99%